1999
DOI: 10.1017/s0140525x9900182x
|View full text |Cite
|
Sign up to set email alerts
|

Words in the brain's language

Abstract: If the cortex is an associative memory, strongly connected cell assemblies will form when neurons in different cortical areas are frequently active at the same time. The cortical distributions of these assemblies must be a consequence of where in the cortex correlated neuronal activity occurred during learning. An assembly can be considered a functional unit exhibiting activity states such as full activation (“ignition”) after appropriate sensory stimulation (possibly related to perception) and continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

52
620
8
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,114 publications
(693 citation statements)
references
References 407 publications
(438 reference statements)
52
620
8
13
Order By: Relevance
“…However, the significance of this association has been controversial. Citing its proximity to neural circuits known to subserve motor planning, some researchers have proposed that the left prefrontal cortex is activated during the retrieval of action words [43,54], not of verbs as such. Others have noted that left frontal evoked potentials are observed in response to non-action verbs as well as action verbs [16], and a recent study using repetitive transcranial magnetic stimulation (rTMS) showed that suppression of the left prefrontal cortex in normal subjects induces selective delays in responses to verb and pseudo-verb processing tasks very similar to the ones used here [50].…”
Section: Neuroanatomical Correlates Of Grammatical Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the significance of this association has been controversial. Citing its proximity to neural circuits known to subserve motor planning, some researchers have proposed that the left prefrontal cortex is activated during the retrieval of action words [43,54], not of verbs as such. Others have noted that left frontal evoked potentials are observed in response to non-action verbs as well as action verbs [16], and a recent study using repetitive transcranial magnetic stimulation (rTMS) showed that suppression of the left prefrontal cortex in normal subjects induces selective delays in responses to verb and pseudo-verb processing tasks very similar to the ones used here [50].…”
Section: Neuroanatomical Correlates Of Grammatical Processingmentioning
confidence: 99%
“…Some patients are poor at naming verbs relative to nouns [4,6,9,33,35], while others are worse at naming nouns than verbs [2,35,47,56]. But these deficits have most often been interpreted as resulting from damage to sensorimotor networks that store or mediate access to conceptual knowledge about objects and actions [12,43,54]. By contrast, relatively little discussion has focused on the possibility that they reflect the loss of neural representations of nouns and verbs as morphological types [9,50,51], and no attempt has been made to characterize such putative representations at the level of cortical function, in spite of the crucial role that grammatical category information plays in language processing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, metalinguistic tasks associated to go/no go paradigms have been largely used since the first ERP studies on speech production with healthy subjects (Jescheniak, Schriefers, Garrett, & Friederici, 2002;Rodriguez-Fornells, Schmitt, Kutas, & Münte, 2002;Schmitt, Münte, & Kutas, 2000;Van Turennout, Hagoort, & Brown, 1998, 1999Zhang & Damian, 2009) and with brain damaged (aphasic) speakers Hensel, Rockstroch, Berg, & Schonle, 2004). Besides the drawback of using a metalinguistic task to study speech production, the interpretation of such results in terms of time-course of the addressed encoding processes is problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Lexical frequency was a strong predictor of word production latencies in many studies using word reading (e.g., Gerhand & Barry, 1998;1999see Andrews & Heathcote, 2001 for a review) or picture naming tasks (e.g., Bonin, Fayol & Gombert, 1998;Jescheniak & Levelt, 1994;Oldfield & Wingfield, 1965). However, the reliably of lexical frequency effects has been challenged since effects of word AoA have also been reported (e.g., Bonin, Fayol, & Chalard, 2001;Bonin, Chalard, Méot, & Fayol, 2002;Chalard, Bonin, Méot, Boyer, & Fayol, 2003;Morrison, Ellis, & Quinlam, 1992;Morrison & Ellis, 1995).…”
mentioning
confidence: 99%
“…For example, goal representations have a crucial role in the planning and control of action, and action understanding and imitation are performed at the goal rather than at the movement level (Iacoboni et al, 2005;Wohlschläger, Gattis,& Bekkering, 2003). Moreover, it has been shown that these apparently unrelated abilities and others which were believed to be in the realm of abstract thought, such as language understanding, share common representational structures and mechanisms in the brain and involve signiWcant use of the motor system (Fadiga, Craighero, Buccino, & Rizzolatti, 2002;Pulvermüller, 1999). Recent studies have revealed the crucial role of canonical and mirror neurons (Rizzolatti & Craighero, 2004;Rizzolatti et al, 1988) and internal forward models (Kawato, 1999;Wolpert & Ghahramani, 2004) in most of the aforementioned tasks.…”
mentioning
confidence: 99%